Coastal Adaptation of the Tidal flood in Kaliwlingi Village, Indonesia - vindiawati tontoiyo (USN Kolaka, 2020)
The coastal region is one of the areas directly affected by climate change. Coastal communities are the ones with the highest level of vulnerability to the effects of climate change. Kaliwlingi Village is one of the coastal areas in Brebes Regency which is vulnerable to tidal flood disasters. This study aims to determine the impact of tidal floods in Kaliwlingi Village, Brebes Regency and determine the community's approach to tidal floods. This research uses a qualitative method with a descriptive narrative approach. In this case study the data analysis was obtained from Miles and Huberman's analysis in terms of data reduction, data presentation and conclusion drawing. Based on the results of the study note that tidal floods affect various aspects of life such as physical aspects, economic aspects and environmental aspects. Most people adapt to tidal flooding by raising their houses, making embankments and roadside and planting mangroves.